2009
DOI: 10.1177/112067210901900415
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal Bevacizumab for Treatment of Chronic Central Serous Chorioretinopathy

Abstract: Anatomic and functional improvement following intravitreal bevacizumab injections suggest that vascular endothelial growth factor (VEGF) may be involved in fluid leakage in patients with chronic CSC. The results suggest a possible role for anti-VEGF agents in the treatment of chronic CSC. Further evaluation of intravitreal bevacizumab for chronic CSC in controlled randomized studies is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
64
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(70 citation statements)
references
References 19 publications
(11 reference statements)
2
64
1
Order By: Relevance
“…Most case series reported no specific complications, although there is always some risk of postinjection endophthalmitis. 49 Most studies reported that IVB might be effective in terms of improving visual acuity and reducing CMT without significant complications and can be considered an optional intervention, 1,2,23,24,28,32,33 but these conclusions should be interpreted cautiously owing to the self-limiting nature of acute and even in chronic CSC. Moreover, it should be noted that the aqueous humor and plasma levels of VEGF were not significantly increased in patients with CSC compared with the healthy control group.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Most case series reported no specific complications, although there is always some risk of postinjection endophthalmitis. 49 Most studies reported that IVB might be effective in terms of improving visual acuity and reducing CMT without significant complications and can be considered an optional intervention, 1,2,23,24,28,32,33 but these conclusions should be interpreted cautiously owing to the self-limiting nature of acute and even in chronic CSC. Moreover, it should be noted that the aqueous humor and plasma levels of VEGF were not significantly increased in patients with CSC compared with the healthy control group.…”
Section: Discussionmentioning
confidence: 99%
“…19,40 Recently, anti-VEGF antibody has been used in CSC as an off-label method. [1][2][3][22][23][24]28,30,32,33,[41][42][43] Bevacizumab is a recombinant humanized full-length monoclonal antibody of VEGF that penetrates the retina and is transported into the photoreceptor outer segments, RPE, and choroid after intravitreal injection. 44 The half-life of bevacizumab in the vitreous is 5.6 days, and it remains in the eye for 4 to 6 weeks.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, neurosensory retinal detachment can even be treated with anti-VEGF. 5 This might suggest that not the anti-VEGF-receptor effect of sunitinib was responsible for the neurosensory retinal detachment but other properties of its spectrum of action. …”
mentioning
confidence: 99%